Effect of different brewing times on antioxidant activity and polyphenol content of loosely packed and bagged black teas (Camellia sinensisL.) - Zeinab Nikniaz; Reza Mahdavi; Seyed Jamal Ghaemmaghami; Neda Lotfi Yaghin; Leila Nikniaz (Mashhad University of Medical Sciences, 2016)
Objective: Determination and comparison of the effect of infusion time on the antioxidant activity and total polyphenol contents of bagged and loosely packed black teas. Materials and Methods: For twenty loosely packed and eleven bagged tea samples, the antioxidant activity and total polyphenol content were analyzed using FRAP and Folin-Ciocalteau methods, respectively. The ANOVA with Tukey post-hoc test and independent t-test were used for statistical analysis. Results: The antioxidant activity and polyphenol content of various brands of tea samples were significantly different. There were significant differences in the antioxidant activity of loosely packed teas between 5, 15(p=0.03), 30(p=0.02) and 60(p=0.007) minutes of brewing times. Besides, there was a significant difference in antioxidant activity of bagged samples infused for 1 minute with four other infusion time points (p